Replacing fishmeal with an insect meal blend: Implications for intestinal microbiota in European seabass - Violeta Kalemi; Simona Rimoldi; Rafaela S. Costa; Ana Basto; Marta Monteiro; Genciana Terova; Luisa M.P. Valente (Aquaculture Reports)
In this study, we investigated the effects of an insect meal (IM) blend containing larvae of Hermetia illucens and Tenebrio molitor on the gut microbiota of European seabass (Dicentrarchus labrax), a key species in Mediterranean marine aquaculture. This research stands out by examining a combination of IMs rather than a single source, thereby addressing an underexplored area in the current literature. In a feeding trial that lasted 75 days, European seabass were fed three different diets: a commercial-like control diet and two experimental diets containing partial replacement of FM with IM (25 % and 50 %). The experimental diets showed no adverse effects on feed intake or overall fish health. Analysis of the microbiota revealed significant changes in gut microbial communities, with a trend towards increased bacterial richness and diversity in fish fed IM. Beta diversity analysis showed that the mucosa-associated microbial communities were stable across diets, while the digesta-associated microbiota showed notable shifts in the IM25 and IM50 groups, suggesting that the transient microbiota is more sensitive to dietary changes. The study also found an enrichment of beneficial bacterial genera, particularly Bacillus and Paenibacillus, in fish fed IM. These genera, known for their chitinolytic activity, have likely adapted to the increased chitin content in IM diets. Oceanobacillus (Bacillaceae) and Brevibacterium (Brevibacteriaceae) were more abundant in the digesta of fish from the IM25 and IM50 groups, but not in the mucosa. Their presence indicates that they react more strongly to changes in diet than to a stable mucosal environment. Overall, the study highlights the potential of an IM-based diet to support fish health and growth while promoting a favorable gut microbiota.